Implementation of Regional Expansion Policy in Indonesian Territory: A Cost and Benefit Perspective - Julizar Idris; Jumanah Jumanah; Iwan Setiawan; Anita Tina; Ficka Yulia Badariyah; Sri Wahyuningsih (Department of Public Administration, 2023)
Cost and benefit analysis is carried out to assess whether the costs associated with financing a feasibility study outweigh the potential benefits. Cost refers to the financial resources used in conducting the study, while benefits cover possible risks of project failure, including opportunity costs, start-up costs, and capital costs. A comprehensive evaluation is carried out to determine whether the costs associated with funding the feasibility study outweigh the potential benefits. This research approach uses a qualitative approach, where the method focuses on research by describing the phenomena that occur. The type of research used is descriptive. Data collection with biometric mapping was carried out on the VOSViewer application, then, in the text format of the data, which was inputted and analyzed with VOSViewer, the results of research developments in the implementation of the smart city program obtained the conclusion. The results of the expansion of the regions revealed the gloomy situation of the government's performance and the development of the public in the 70 regions resulting from the expansion. In addition, the process of regional expansion is the strengthening of ethnic and religious identity politics and the rise of narrow regional insights. Regional expansion is the best solution for every problem that occurs in the region. The creation of justice and equity between the central and regional governments. The formation of new autonomous regions is expected to bring services closer to the community, the implementation of an effective and efficient government wheel and democratization at the regional level.